(untitled) (Research, Society and Development, 2020)
The need for information on rainfall of certain durations and frequencies is very large in various hydraulic designs. Thus, the objective of this work is to adjust the cumulative Gumbel probability function to obtain the maximum expected precipitation intensities for different return periods, obtaining the intensity-duration-frequency equation by means of the isozone method for maximum annual daily rainfall data. In this case, the rainfall data from the Newton Belo rainfall gauge station between 1985 and 2013 were adopted. A series of maximum rainfall intensity for one day of precipitation was elaborated using the Gumbel methodology. The extreme values for the return periods of 5, 10, 20, 30, 50 and 100 years were estimated by the isozone method, adjusting the IDF curve, which was compared to IDF curves of the Northeast and Southeast region of Brazil, showing good estimate for rainfall intensities. This comparison suggests that the generated equation can be used to calculate the maximum rainfall intensity with different durations and return periods for hydraulic and water resources engineering studies in the Governador Newton Bello region.